Rehabilitate heritage or schooling the population? Public expenditure in the middle century of Sevilla - Daza Sierra, Antonio J. (Hispania Nova, 2021)
This article reflects about the provision of public educational services in the city of Seville during the Moderate Decade, highlighting the contradiction between national legislation and local practice in the creation and operation of state schools. The analysis of the municipal documentation demonstrates how the obligations of the city councils increased accompanied by budgetary restrictions. The decisions of local authorities ultimately benefited the interests of the urban elite, and the scarce funds for primary education were diverted towards the rehabilitation of buildings and the establishment of secondary schools, to the detriment of the needs of the working class and contravening national regulations.